2020
DOI: 10.1186/s12915-020-00848-7
|View full text |Cite
|
Sign up to set email alerts
|

A molecular insight into the dissociable regulation of associative learning and motivation by the synaptic protein neuroligin-1

Abstract: Background In a changing environment, a challenge for the brain is to flexibly guide adaptive behavior towards survival. Complex behavior and the underlying neural computations emerge from the structural components of the brain across many levels: circuits, cells, and ultimately the signaling complex of proteins at synapses. In line with this logic, dynamic modification of synaptic strength or synaptic plasticity is widely considered the cellular level implementation for adaptive behavior such as learning and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…Previous work indicated mice lacking Nlgn1 showed no changes across numerous behavioural measures including anxiety-like behaviours in the elevated plus maze, but displayed impaired spatial learning and memory in the Morris water maze (Blundell et al, 2010). We have recently shown, through a deep cognitive characterisation using a series of touchscreen-based assays, that while associative learning was not impacted due to loss of Nlgn1, motivated behaviour and cost-reward processing was consistently disrupted (Luo et al, 2020), having implications for mood disorders. Whilst postsynaptic mechanisms are likely a major driver to this altered behaviour, changes to endocytosis may also contribute to these effects.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous work indicated mice lacking Nlgn1 showed no changes across numerous behavioural measures including anxiety-like behaviours in the elevated plus maze, but displayed impaired spatial learning and memory in the Morris water maze (Blundell et al, 2010). We have recently shown, through a deep cognitive characterisation using a series of touchscreen-based assays, that while associative learning was not impacted due to loss of Nlgn1, motivated behaviour and cost-reward processing was consistently disrupted (Luo et al, 2020), having implications for mood disorders. Whilst postsynaptic mechanisms are likely a major driver to this altered behaviour, changes to endocytosis may also contribute to these effects.…”
Section: Discussionmentioning
confidence: 87%
“…All procedures were approved by the Florey Animal Ethics Committee and performed in accordance with the guidelines of the National Health and Medical Research Council Code of Practice for the Care and Use of Animals for Experimental Purposes in Australia. Heterozygous Nlgn +/− mice were obtained from Prof. Nils Brose (Varoqueaux et al, 2006) and backcrossed on a C57BL/6 background as described (Luo et al, 2020). Nlgn1 −/− mice and WT littermate controls were generated at The Florey by mating Nlgn +/− females and males.…”
Section: Hippocampal Neuronal Culturesmentioning
confidence: 99%
“…Previous work indicated mice lacking Nlgn1 showed no changes across numerous behavioural measures including anxiety-like behaviours in the elevated plus maze, but displayed impaired spatial learning and memory in the Morris Water Maze (Blundell et al, 2010). We have recently shown, through a deep cognitive characterization using a series of touchscreen-based assays, that while associative learning was not impacted due to loss of Nlgn1, motivated behaviour and cost-reward processing was consistently disrupted (Luo et al, 2020), having implications for mood disorders. Whilst postsynaptic mechanisms are likely a major driver to this altered behaviour, changes to endocytosis may also contribute to these effects.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, in addition to our key measures of learning, we examined latencies to make correct and incorrect responses, as well as to collect rewards. While most studies employing the touchscreen visual discrimination and reversal learning tasks commonly report latencies pooled across sessions for the whole task (task‐level), we sought to assess latencies at both task (Figures S4 and S5) and session‐by‐session levels (Figures 4 and 5) as we have previously seen response latencies, but not reward collection latencies, alter with the progression of testing on tasks 18,40 …”
Section: Resultsmentioning
confidence: 99%
“…A large‐scale mouse genetic screen of loss‐of‐function mutations in postsynaptic proteins showed that mutations in PSD‐95 and its close interacting proteins had the strongest phenotypes in synaptic electrophysiology and behaviour, indicating that PSD‐95 protein complexes are critical components of the postsynaptic terminal of excitatory synapses 16,17 . While many studies have investigated changes in measures of synaptic signalling and plasticity following mutations in genes encoding postsynaptic proteins, we know less about their roles in complex cognitive behaviour, especially given physiological phenotypes do not always map directly to distinct behavioural measures (e.g., impaired long‐term potentiation does not always predict learning performance) 18 …”
Section: Introductionmentioning
confidence: 99%